Dynamic changing smoking habits and cardiovascular events in patients newly diagnosed with hypertension, diabetes, or dyslipidemia: a national cohort study - Song, Shinjeong; Lee, Hye Ah; Kim, Yeji; Jeon, Bo Kyung; Moon, Chang Mo; Park, Junbeom (Frontiers in Cardiovascular Medicine, 2023)
Background and Aims This study aimed to examine the association between dynamic smoking habit change and cardiovascular risk in a population newly diagnosed with hypertension, diabetes, and dyslipidemia. Methods A total of 49,320 individuals who had undergone health examinations provided by the Korea National Health Insurance Service were included in this study. Multivariable Cox proportional hazard models were performed to determine the hazard ratios (HRs) and 95% confidence intervals (CIs) of incident MACE and all-cause mortality according to dynamic smoking habit change for 2 years. Results During the follow-up, there were 1004 (2.2%), 3483 (7.6%), and 334 (0.7%) cases of myocardial infarction, stroke events, and cardiovascular death, respectively. The group with worsening smoking habits had an increased risk of cardiovascular events and death (HR: 1.33, 95% CI: 1.26–1.40) compared to improved smoking habits. The robustness of the results determined by a series of sensitivity analyses further strengthened the main findings. Conclusions Our findings suggest that worsening of smoking habits, even for a short period of time, may increase the risk of myocardial infarction, stroke, and cardiovascular death in patients diagnosed with hypertension, diabetes, and dyslipidemia. For the primary prevention of cardiovascular events in patients with underlying diseases, dynamic modification of smoking habits should be actively considered.